Assessment of African elephant (Loxodonta africana) molars and mandibles and their association with estimated age and sex - Fiona Stansfield (Pachyderm)
Introduction: Estimates of an elephant’s age are made by observing the movement of their molars through the mandible. Established ageing techniques have produced varying results and problems have been exacerbated by the difficulty of molar identification. Molar identification is made easier when the sex of the individual is known, as male teeth tend to be larger than female teeth. Elephant mandibles (n = 323) and molars of Zimbabwean origin where gender was known were studied in an attempt to identify relationships between molar/mandible size and sex. Measurements of molars and mandibles were recorded.